2020
DOI: 10.1177/0363546520961160
|View full text |Cite
|
Sign up to set email alerts
|

Lumbosacral Transitional Vertebrae Predict Inferior Patient-Reported Outcomes After Hip Arthroscopy

Abstract: Background: While the association between spinal disease and hip arthroplasty outcomes has been well studied, there is less known about the effect of spinal pathology in hip arthroscopy (HA) outcomes. Lumbosacral transitional vertebrae (LSTV) are anatomic variations where caudal vertebrae articulate or fuse with the sacrum or ilium. Hypothesis: LSTV can lead to inferior outcomes after HA for treatment of femoroacetabular impingement. Study Design: Cohort study; Level of evidence, 3. Methods: We retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Limited spinal mobility remains a poorly recognized clinical entity in hip preservation. In a critical evaluation of the current literature, the majority of studies drew comparisons between patients with lumbar spine pathology or anatomic variants against a control group of patients without known lumbar spine disease [ 6 , 7 , 16 ]. These studies have demonstrated that preexisting lumbar pathology may adversely affect outcomes after hip arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited spinal mobility remains a poorly recognized clinical entity in hip preservation. In a critical evaluation of the current literature, the majority of studies drew comparisons between patients with lumbar spine pathology or anatomic variants against a control group of patients without known lumbar spine disease [ 6 , 7 , 16 ]. These studies have demonstrated that preexisting lumbar pathology may adversely affect outcomes after hip arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Heaps et al . [ 16 ] reported that patients with lumbosacral transitional vertebrae (LSTV) had less benefit after hip arthroscopy as demonstrated by lower patient-reported outcome scores (PROs) 24–35 months postoperative compared to patients without LSTV. In their paper they proposed the importance of lumbosacral motion loss on outcomes in hip arthroscopy due to the possibility of residual FAI even after surgical correction.…”
Section: Introductionmentioning
confidence: 99%
“…These findings differ from other reports in the literature, although this difference is hardly irreconcilable. Heaps et al 18 recently reported less benefit of hip arthroscopy in patients with LSTV, with patients with LSTV having significantly lower patient-reported outcomes measures 5 to 11 months postoperatively, 12 to 23 months postoperatively, and 24 to 35 months postoperatively versus patients without LSTV. We would certainly benefit from further study to understand why patients with LSTV did worse than that of the current study by Luo et al, but it is important to note that a significantly greater proportion of patients with LSTV had Castellvi type 3 or 4 on this study (52% of patients included with LSTV) compared with the study by Luo et al (7.7% of patients included with LSTV).…”
Section: See Related Article On Page 149mentioning
confidence: 99%
“…We would certainly benefit from further study to understand why patients with LSTV did worse than that of the current study by Luo et al, but it is important to note that a significantly greater proportion of patients with LSTV had Castellvi type 3 or 4 on this study (52% of patients included with LSTV) compared with the study by Luo et al (7.7% of patients included with LSTV). 17,18 This difference between cohorts may highlight the importance of lumbosacral motion loss on hip outcomes. This is in line with biomechanical and finite element studies that show that even with more stiffness, low-grade transitional vertebrae do retain some degree of mobility that may not be present in those with fused vertebrae.…”
Section: See Related Article On Page 149mentioning
confidence: 99%
“…Much additional clinical hip arthroscopy research has sought to identify other factors that might predict surgical outcomes, including general patient characteristics, preoperative hip anatomy, and preoperative or early postoperative pain or PROM levels. 5,11,13,[17][18][19][20] Most of these studies have been retrospective in design, so they identify associations that would need to be verified as truly predictive in future prospective studies. As New York Yankee great Yogi Berra is reported to have said, ''It's tough to make predictions, especially about the future.''…”
mentioning
confidence: 99%